Altered body schema processing in frontotemporal dementia with C9ORF72 mutations. Issue 9 (12th February 2014) - Downey, Laura E; Fletcher, Phillip D; Golden, Hannah L; Mahoney, Colin J; Agustus, Jennifer L; Schott, Jonathan M; Rohrer, Jonathan D; Beck, Jonathan; Mead, Simon; Rossor, Martin N; Crutch, Sebastian J; Warren, Jason D
Abstract : Background: Mutations in C9ORF72 are an important cause of frontotemporal dementia (FTD) and motor neuron disease. Accumulating evidence suggests that FTD associated with C9ORF72 mutations (C9ORF72-FTD) is distinguished clinically by early prominent neuropsychiatric features that might collectively reflect deranged body schema processing. However, the pathophysiology of C9ORF72-FTD has not been elucidated. Methods: We undertook a detailed neurophysiological investigation of five patients with C9ORF72-FTD, in relation to patients with FTD occurring sporadically and on the basis of mutations in the microtubule-associated protein tau gene and healthy older individuals. We designed or adapted behavioural tasks systematically to assess aspects of somatosensory body schema processing (tactile discrimination, proprioceptive and body part illusions and self/non-self differentiation). Results: Patients with C9ORF72-FTD selectively exhibited deficits at these levels of body schema processing in relation to healthy individuals and other patients with FTD. Conclusions: Altered body schema processing is a novel, generic pathophysiological mechanism that may link the distributed cortico-subcortical network previously implicated in C9ORF72-FTD with a wide range of neuropsychiatric and behavioural symptoms, and constitute a physiological marker of this neurodegenerative proteinopathy.